The 'Duce hometown effect' on local industrial development: The case of Forlì. Issue 4 (18th May 2020) - Fauri, Francesca; Troilo, Matteo
Abstract: The history of fascist intervention and rescue in support of Italian banks and firms (either through nationalisation or direct aid) in the inter-war years is well known. The case of Forlì adds an important piece of information to the broad literature on state-sponsored development. Benito Mussolini was born in Predappio, a small village in the Apennines in the province of Forlì. And Forlì was meant to become 'la città del Duce' ('the Duce's hometown'). The case of Forlì offers an original perspective: entrepreneurs who chose Mussolini's hometown to obtain special concessions, a novel element in the crowded panorama of special relationships between government and industry in Italy. But on the other hand, this article will also underline the unsuitability of big business to local economic characteristics (and post-war challenges) and the return to a traditional growth path centred around the small-firm model specialising in traditional sectors and family-owned, centralised management. State-sponsored business failed and provided no stimulus to local growth: any talk of 'industrial continuity' in Forlì requires us to acknowledge that it is based on the steady presence and continuous regeneration of locally grown, small family businesses.